High Performing Work System and Emotional Intelligence among Working Women - Nematullah Islmzai (International Journal of Engineering and Management Research, 2023)
The study aims to understand how the implementation of HPWS influences the development of emotional intelligence in female employees and how this relationship, through a literature review, empirical analysis, and case studies, this paper provides insights into the significance of integrating HPWS and EI in the workplace, shedding light on strategies to empower working women. As gender disparities persist in contemporary workplaces, the need to comprehend the mechanisms by which HPWS can potentially enhance EI, thereby bolstering the performing and well-being of female employees, has become increasingly imperative. By drawing from a multitude of research approaches, this paper synthesizes and advances our understanding of these multifaceted interconnections and elucidates the symbiotic relationship between HPWS and EI in the context of female employees within the workforce. It underscores the imperative for organizations to adopt strategies that encourage the development of emotional intelligence among women, not only as a means of promoting gender equality but also as a viable pathway to enhance job performing and overall well-being. By integrating a multifaceted research approach, this study contributes to the academic discourse and provides practical guidance for organizations aiming to foster an inclusive and empowered workplace for women.